Application of Intuitionistic Type-2 Fuzzy Set on Flat EEG Image - Suzelawati Zenian (Atlantis press, 2023)
In this paper, the Flat EEG images are enhanced based on intuitionistic type-2 fuzzy set. The non-membership function is defined by Sugeno type intuitionistic fuzzy generator. Moreover, a new membership function is defined by using Hamacher t-conorm. Experimental results show that the method provides better results compared to classical and fuzzy methods.